Shrinking share of middle-income group in Germany and the US - Markus M. Grabka; Jan Goebel; Carsten Schröder; Jürgen Schupp (DIW Economic Bulletin, 2016)
According to calculations based on the Socio-Economic Panel (SOEP) study, the proportion of middle-income group in Germany fell by six percentage points from 1991 to 2013, taking it to 54 percent. Germany is not the only country to have experienced such a downturn, however. Analyses of the situation in the US indicate a similar decline. To the middle-income group belong individuals in households earning a total income, before tax and social security contributions, of 67 to 200 percent of the median. In the US, however, there has been a stronger increase in income polarization than in Germany: in the US, those who have left the middle-income group tend to be concentrated more on the periphery of the income distribution. The share of income of the middle-income group has also dropped substantially in both countries studied. This decline affected all age groups with the exception of individuals of people at retirement age. In the US, it was primarily immigrants from Latin America who tended to move down from the middle-income group, while in Germany, the most notable decline was seen in the share of foreigners in the middle-income bracket. However, when looking at the personal wealth of the middle-income group, patterns differ: while in the US, this group experienced a decline in real net worth of over 25 percent, in Germany it experienced an increase of 15 percent in real terms.
Keywords: D31; I31; I32; 330; Middle class; Inequality; Polarization; SOEP